Diabetic Retinopathy in Pregnancy: A Review (Bangladesh Journal of Obstetrics & Gynaecology, 2016)
Pregnancy in a diabetic woman brings about many changes that can lead to the development of diabetic retinopathy (DR) or worsening of pre-exi ing disease. In some patients this may develop into sight threatening disease, which if not treated adequately, can cause deva ating visual impairment. There is a lack of e ablished guidelines for screening these patients during pregnancy. In this article we discuss the physiological changes during pregnancy that contribute to worsening of diabetic retinopathy and review the relative contribution of risk factors to the underlying pathological processes. It is important to identify and treat any preexi ing retinopathy in diabetic women considering pregnancy and optimise glycaemic control prior to conception. Rapid tightening of glycaemic control after conception is associated with a less favourable outcome. Based on the exi ing literature we sugge  guidelines for diabetic retinopathy screening for women during pregnancy. E ablished sight-threatening retinopathy should be treated at an earlier  age in pregnant women compared to non-pregnant diabetics with a similar disease.Bangladesh J Obstet Gynaecol, 2014; Vol. 29(1) : 37-42